Surface-engineered vanadium nitride nanosheets for an imaging-guided photothermal/photodynamic platform of cancer treatment. Issue 4 (15th January 2019) - Yang, Chunyu; Yu, Huahai; Gao, Yan; Guo, Wei; Li, Zizuo; Chen, Yaodong; Pan, Qinmin; Ren, Mingxing; Han, Xiaojun; Guo, Chongshen
Abstract : VN nanosheets were developed as a brand-new phototherapy agent for photoacoustic imaging-guided photothermal and photodynamic combination oncotherapy. Abstract : Of the many strategies for precise tumor treatment, near-infrared (NIR) light-activated "one-for-all" theranostic modality with real-time diagnosis and therapy has attracted extensive attention from researchers. Herein, a brand-new theranostic nanoplatform was established on versatile vanadium nitride (VN) nanosheets, which show significant NIR optical absorption, and resultant photothermal effect and reactive oxygen species activity under NIR excitation, thereby realizing the synergistic action of photothermal/photodynamic co-therapy. As expected, systematic in vitro and in vivo antitumor evaluations demonstrated efficient cancer cell killing and solid tumor removal without recurrence. Meanwhile, the surface modification of VN nanosheets with poly(allylamine hydrochloride) and bovine serum albumin enhanced the biocompatibility of VN and made it more suitable for in vivo delivery. Moreover, VN has been ascertained as a potential photoacoustic imaging contrast for in vivo tumor depiction. Thus, this work highlights the potential of VN nanosheets as a single-component theranostic nanoplatform.